Psycholinguistics In a Digital Perspective: The Influence of social media On Language Production - Rini Lubis; Muhammad Hasyimsyah Batubara hasyimsyah (Advances In Education Journal, 2025)
The rapid advancement of digital technology has brought significant changes to the way people interact and use language, particularly through social media, which has now become a major space for self-expression and shaping linguistic habits. This study aims to analyze the influence of social media on human language production from a psycholinguistic perspective. The research was conducted using a descriptive qualitative approach through digital observations and semi-structured interviews with fifth-semester students of the English Education Program. The findings indicate that social media affects students’ language production in several ways: sentence structures become simpler, register shifts occur, language is produced more quickly, and academic accuracy tends to decrease. Nevertheless, students are still able to adapt and return to using formal language when required by the context. These findings also open opportunities for further research on how digital habits relate to academic literacy skills.